Kualitas Pelayanan Publik Dinas Perpustakaan Dan Kearsipan Provinsi Sulawesi Selatan - Risda B. Kulibang; Ansyari Mone; Muhammad Amril Pratama Putra (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
Abstract : This study aims to determine the Quality of Public Services of the Library and Archives Service of South Sulawesi Province. The research method used is a descriptive method with a qualitative approach, while the data collection method is through observation, interviews and documentation. The results of this study indicate that the Quality of Public Services of the Library and Archives Service of South Sulawesi Province, based on 5 indicators according to Zeithaml regarding the quality of public services, namely 1) Physical evidence (tangible) of the provision of physical facilities in the library such as air conditioning, tables, computers, and mobile library services, as well as active promotion through social media 2) Reliability, namely services that are fairly consistent, timely, and equal to all visitors 3) Responsiveness is seen from the quick response of employees to visitor needs, 4) Assurance, namely consistent services according to Standard Operating Procedures (SOP) provide a sense of security and trust for visitors 5) Empathy is seen from employee participation in various literacy activities in 24 Regencies/Cities.